THE STRATEGY OF ANTIMICROBIAL THERAPY OF ACUTE UNCOMPLICATED PYELONEPHRITIS FROM THE POSITION OF ETIOLOGICAL DATA - A. D. Kaprin; A. A. Kostin; S. V. Popov (Исследования и практика в медицине, 2015)
Abstract:Acute pyelonephritis is one of the common diseases both in outpatient and in the hospital practice. The leading causative agent of this disease is E. coli. Obstructive uropathy, foreign body, vesicoureteral reflux, sexual activity, use of local contraceptives contribute to the upward development of urinary infection. The goals of antimicrobial therapy for acute uncomplicated pyelonephritis are: relief of symptoms, restoration of social activity, prevention of complications and relapse prevention. The choice of an antimicrobial agent in most cases is carried out empirically based on the data on the dominant pathogens and their regional resistance. In acute uncomplicated pyelonephritis duration of antimicrobial therapy should be 7–14 days. The drugs of choice for treatment of acute uncomplicated pyelonephritis non-severe in adults are ciprofloxacin and levofloxacin, ceftibuten and cefixime. Patients with acute uncomplicated pyelonephritis severe emergency hospitalization is shown in urological outpatient and parenteral antimicrobial therapy (carbapenems or protected aminopenicillins combined with or without amikacin) with subsequent conversion to oral drugs and infusion therapy.